2022
DOI: 10.3389/fmolb.2022.884705
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis and Conformational Dynamics of Short Helical Hyperphosphorylated Segments of Tau Protein (Sequence 254–290) in Alzheimer’s Disease: A Molecular Dynamics Simulation Study

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder whose early diagnosis leads to a chance for successful treatment and decreases the side effects. Hyperphosphorylation of tau proteins is a pathological hallmark of AD that causes it to lose its attachment ability to the microtubules. Alteration of tau structure due to its hyperphosphorylation is an exciting challenge regarding AD treatments. Here, we aimed to examine the structural alterations of short helical segments of tau protein with one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…By performing the combination of replica exchange MD (REMD) and MD simulations, Derreumaux et al examined the effect of phosphorylated Ser356 on the conformational ensemble of the tau R3–R4 domain dimer and reported that the R3–R4 dimer explored elongated, U-shaped, V-shaped, and globular forms; phosphorylation of Ser356 decreased the population of the β-helix motif spanning residues 336–354 and the intermediates near the fibril-like conformers . The MD simulation study on the tau K254–K290 fragment revealed that the complex with three phosphorylated sites (Ser262, 285, and 289) could form compact and more stable structures than that with one phosphorylated site (Ser262) . Our previous work investigated the influence of acetylation of K280 on the aggregation of PHF6* by performing REMD simulations and found that K280 acetylation strengthened the intermolecular interactions and led to more ordered β-sheet-rich structures .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By performing the combination of replica exchange MD (REMD) and MD simulations, Derreumaux et al examined the effect of phosphorylated Ser356 on the conformational ensemble of the tau R3–R4 domain dimer and reported that the R3–R4 dimer explored elongated, U-shaped, V-shaped, and globular forms; phosphorylation of Ser356 decreased the population of the β-helix motif spanning residues 336–354 and the intermediates near the fibril-like conformers . The MD simulation study on the tau K254–K290 fragment revealed that the complex with three phosphorylated sites (Ser262, 285, and 289) could form compact and more stable structures than that with one phosphorylated site (Ser262) . Our previous work investigated the influence of acetylation of K280 on the aggregation of PHF6* by performing REMD simulations and found that K280 acetylation strengthened the intermolecular interactions and led to more ordered β-sheet-rich structures .…”
Section: Introductionmentioning
confidence: 99%
“…42 The MD simulation study on the tau K254−K290 fragment revealed that the complex with three phosphorylated sites (Ser262, 285, and 289) could form compact and more stable structures than that with one phosphorylated site (Ser262). 43 Our previous work investigated the influence of acetylation of K280 on the aggregation of PHF6* by performing REMD simulations and found that K280 acetylation strengthened the intermolecular interactions and led to more ordered β-sheet-rich structures. 44 In this study, we focused on the early aggregation process of PHF6 peptides and explored the potential effect of the phosphorylation of Y310 on the PHF6 oligomerization.…”
Section: ■ Introductionmentioning
confidence: 99%